Implementasi Kurikulum Merdeka Pembelajaran PAI Pada Siswa Kelas Tujuh di SMP Bhinneka Tunggal Ika Sengon Agung Purwosari Pasuruan - Siti Fatimah Putri; M Jamhuri; Achmat Mubarok; Achmad Yusuf (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
As time progresses, there are also changes in the educational component, such as changes to the curriculum, the Ministry of Education and Culture has officially announced the latest curriculum entitled independent learning, which will be implemented starting in the 2022/2023 academic year in all educational units independently. The aim of this research is to describe the implementation of the independent curriculum in Islamic Religious Education learning at BHINNEKA TUNGGAL IKA SMP and to reveal the positive impacts and obstacles experienced in implementing the independent curriculum in Islamic Religious Education learning at BHINNEKA TUNGGAL IKA SMP SENGON AGUNG PURWOSARI PASURUAN. This research uses a phenomenological approach and the method used is a qualitative field study type. Data collection techniques were carried out through observation, interviews and documentation studies. then analyzed with stages of condensation, presentation and drawing conclusions. The results of the research show that the independent curriculum implementation process is broken down into three stages, namely planning, implementation and evaluation. The positive impacts of implementing the independent curriculum on Islamic Religious Education learning include increasing teacher and student creativity, increasing student enthusiasm and activeness in learning, and increasing teacher enthusiasm in developing their own capacity. Obstacles in implementing the independent curriculum in Islamic Religious Education learning are the difficulty of educators in creating fun and quality learning and determining the right themes and content for P5 activities to suit students' interests and talents and the lack of adequate infrastructure for teaching and learning activities.